Physiological basis of stretching study in the training system of young football players - Tarabrina, N. Yu.; Kraev, Yu. V. (The Russian Journal of Physical Education and Sport, 2018)
For a successful game in football it is necessary to develop the main physical qualities and improve all functional systems of the athletes` organism. It is possible only owing to many-sided physical training, when together with the main physical qualities development attention is paid to football players` special qualities development. The article gives physiological substantiation of muscle relaxation role in the mechanism of young football-players` accuracy of movements formation. Materials. Myotonic and coordinating indices are studied among 22 young athletes, who are 8-12 years old. All respondents trained according to specially created three-week program. It included the exercises for paravertebral muscles and lower extremities muscles stretching. Methods. Information sources analysis and summarizing, electromyotonometry, pedagogical experiment, methods of mathematical statistics. Results. It is shown that stretching exercises fulfillment decreases myotonus among all the respondents in the following points: V37, E 32, V52, V 57 (sinister ? dexter) from 3,52% till 9,76% (p<0,05-0,001).The most susceptible to such kind of influence turned out to be calf muscles and a front surface of the hip, less susceptible turned out to be lumbar part of the muscle, which straightens the spine. Myogenic tonus decrease leads to the quality of movements improvement accuracy from 25,0 till 37,05% (p<0,05). 11-12-year-old football players had the same myovisceral reactions as 8-9-year-old athletes, however, the degree of these reactions intensity was more considerable. Conclusion. The expediency of stretching use was considered. We proved the necessity to use this methodology during transfer and preparatory period of sports training among young football players.